Gowie Corby plays chicken - Kemp, Gene. ([S.l.] : Collins Educational, 1979)
Gowie believes he should trust no one and should want no friends until he encounters the remarkable Rosie Angela Lee.
Keywords: Friendship -- Fiction; Schools -- Fiction